Teaching of a Professional Foreign Language Communication at Higher Institutions of Ukraine - Mudra, Olena; Tonenchuk, Tetiana (Видавничий дім «Гельветика», 2023)
This article addresses the imperative for a significant enhancement of the Ukrainian higher education system to cultivate specialists proficient in conducting professional interactions through foreign language communication across diverse contexts. It delineates the objective of imparting professional foreign language communication skills in universities, emphasizing the attainment of a proficiency level conducive to practical application in subsequent professional endeavors. To enhance the efficiency of the teaching process, educators are urged to develop novel organizational frameworks and methodological techniques. In alignment with the ongoing efforts to elevate the quality of higher education, this article directs its focus toward the development of the professional communicative competence of future specialists, encompassing intercultural, humanities, social, and linguistic components. Within this context, the acquisition of Foreign Language for Specific Purposes assumes paramount importance, facilitating students' rapid adaptation to the evolving challenges presented by academic and professional communities. This development not only garners interest among university instructors but also resonates with learners. The article underscores a dual-focused educational approach, examining two methodologies: English Language for Specific Purposes and Content Language Integrated Learning. It explores potential avenues for optimizing and modernizing the methodology of teaching professional foreign language communication. Furthermore, it highlights the significance of the process of integrating foreign language and professional components, essential for shaping a competitive model of a graduate-specialist in the global labor market. A novel approach to the selection of learning content is advocated within the context of professionally oriented foreign language teaching. The article provides a detailed description of all facets of professionally oriented foreign language teaching, offering a comprehensive overview of the intricacies involved in imparting professionally oriented foreign language skills
Keywords: Integrated learning; teaching foreign languages; professional foreign language communication